Stakeholder Synergy among Government, MSME Actors, and Community toward Sharia Well-Being: A Case Study of Medali Mas Woven Ikat MSME in Kediri - Binti Mutafarida; Zulmi Ramdani; Moh. Farih Fahmi; Yopi Yudha Utama; Ning Purnama Sariati; Widya Ratna Sari (Department of Public Administration, 2026)
This study examines how stakeholder synergy contributes to Sharia well-being through Medali Mas Woven Ikat Micro, Small, and Medium Enterprise (MSME) in Kediri City, Indonesia. The study is motivated by the limited number of studies that integrate stakeholder collaboration, Local Economic Development (LED), and maqashid al-shariah perspectives in explaining community welfare through cultural-based MSMEs. While previous studies have largely focused on economic and social outcomes, limited attention has been given to multidimensional well-being encompassing religious, intellectual, health, and intergenerational dimensions. A descriptive qualitative approach was employed using observations, open-ended interviews, and documentation. Informants consisted of MSME owners, permanent and freelance employees, community members, and representatives from Bank Indonesia and the Kediri City Government. Data were analyzed through data reduction, data display, and conclusion drawing, while source triangulation was applied to enhance the trustworthiness of the findings. The findings indicate that stakeholder synergy among government institutions, Medali Mas Woven Ikat MSME, and the Bandar Kidul community contributes to Sharia well-being through capital assistance, marketing support, training programs, comparative study visits, and employment creation. Government institutions provide strategic support through policy facilitation, market access, and capacity-building programs, while MSMEs serve as drivers of local economic development through innovation and job creation. Community participation strengthens the sustainability of these initiatives by supporting production activities and participating in empowerment programs. These collaborative efforts contribute to the dimensions of maqashid al-shariah, namely religious well-being (ad-din), personal well-being (an-nafs), intellectual well-being (al-aql), wealth well-being (al-mal), and family well-being (an-nasl). This study contributes to the literature by integrating Local Economic Development and maqashid al-shariah perspectives in understanding stakeholder collaboration within cultural-based MSME development and its contribution to multidimensional community well-being.